A comparative study to access the impact of TAP block with wound infiltration in laparoscopic cholecystectomy - Kaushik, Ravi; Kumar, Rajesh; Bafila, Narendra Singh; Verma, Rachna; Gautam, Sanni Deyol (Asian Journal of Medical Sciences, 2024)
Background: The transversus abdominis plane (TAP) block and local anesthetic wound infiltration have been used to relieve pain after laparoscopic cholecystectomy. This study investigated whether the subcostal transversus abdominis block was superior to traditional port-site infiltration of local anesthetic in reducing post-operative pain, opioid consumption, and time for recovery. Aim and Objectives: To investigated whether the subcostal transversus abdominis block is superior to traditional port-site infiltration of local anesthetic in reducing post-operative pain, opioid consumption, and time for recovery. Materials and Methods: All patients were randomly assigned to two equal groups (n=30) using computer-generated randomization. Patients in Group 1 (TAP group) received a TAP block by administration of 10 mL of 0.5% bupivacaine on each side just before completion of surgery, and patients in Group 2 (local wound infiltration [LWI] group) received 10 mL of 0.5% bupivacaine as a local infiltrate at the local site just before completion of surgery. The pain was measured using a Visual Analog Scale (VAS) at intervals of 30 min to 24 h after the procedure. Results: The mean VAS score was significantly lower in group 1 as compared to group 2 at 2 h and 4 h. Whereas the VAS score was not significantly different post-operative 30 min, 6 h, 12 h, and 24 h. The mean first rescue analgesia was significantly more in Group 1 than in Group 2 (P<0.001). Conclusion: The TAP block patients had significant VAS scores at 2 and 4 h postoperatively compared to the LWI patients. The TAP group had a significantly longer median time to first emergency analgesia compared to the LWI group, with a higher proportion of patients requiring only one dose of emergency analgesia.